Cd(II) coordination compounds as heterogeneous catalysts for microwave-assisted peroxidative oxidation of toluene and 1-phenylethanol - Sutradhar, Manas (2020)
The aroylhydrazone Schiﬀ bases 2-hydroxy(2-hydroxybenzylidene)benzohydrazide (H2L1) and 2-amino(2hydroxybenzylidene)benzohydrazide (H2L2) have been used to synthesize the new Cd(II) coordination polymer [Cd(m-1kONO0:2kO:3kO00-L1)(DMF)]n (1) and the dinuclear complex [Cd(1kONO0:2kO-HL2)(kOO0Ac)]2 2DMF (2). Both 1 and 2 have been characterized by elemental analysis, FT-IR and single crystal X-ray diﬀraction analysis. The catalytic performances of 1 and 2 were evaluated towards the microwave (MW) assisted peroxidative oxidation (with tert-butylhydroperoxide, TBHP) of toluene and 1-phenylethanol under heterogeneous conditions. The MW-assisted peroxidative oxidation of toluene by a Cd(II) catalytic system is reported for the first time. At 50 1C, the 2/TBHP/MW catalytic system shows good activity for toluene oxidation with a total (benzaldehyde + benzyl alcohol) product yield of 49% in 1 h, in the absence of any additives. In the case of neat solvent-free peroxidative oxidation of 1-phenylethanol the 1/TBHP/MW catalytic system resulted in 24% total yield of acetophenone under optimized conditions. After the catalytic reactions, both 1 and 2 were successfully recovered and reused.